Pembuatan Aplikasi Wisata Trowulan Berbasis Android - Mangunwijaya, Bernardo Taufiq; Andjarwirawan, Justinus; Handojo, Andreas (Jurnal Infra, 2015)
There are many locations - the historic tourist sites in the area Trowulan very unlikely to miss. Site - historic sites, such as the temple - the temple, goods - goods or equipment - equipment daily life - the era of the Majapahit kingdom, sleeping Buddha statue, the tombs of the ancestors of Majapahit, as well as the ruins of the house - houses kingdom of Majapahit era. Lots of locations - the historic location very missed by the tourists. Even generally in Trowulan location history is not widely known by many people. In general, the tourists searching for information - information through various media, such as on the internet before making a visit. The information obtained is often poorly organized to illustrate the existing tourist sites in Trowulan. With the use of smartphones are widely used today, an application designed to assist travelers in finding the location and information about the location - the tourist sites in Trowulan.This application provides information about tourist sites in Trowulan, referral services for the user to a location, other services is access to information on the location, description of the location, location photo gallery, a list of locations you have visited, running games, and update content. This application is designed to operate on smartphones with Android operating system.Based on testing result, this application is running all functionts that have been mentioned properly, such as login, map, game, stamping, and also content update.